Diffraction analysis of strongly inhomogeneous residual stress depth distributions by modification of the stress scanning method. I. Theoretical concept. (1st October 2015) - Meixner, M.; Fuss, T.; Klaus, M.; Genzel, Ch.
<x xml:space="preserve">Abstract</x> Exploiting the advantages of energy‐dispersive synchrotron diffraction, a method for the determination of strongly inhomogeneous residual stress depth gradients is developed, which is an enhancement of the stress scanning technique. For this purpose, simulations on the basis of a very steep residual stress depth profile are performed, and it is shown that conventional real space evaluation approaches fail, because they do not take into account the variation of the residual stresses within the gauge volume. Therefore, a concept facilitating the deconvolution of the diffraction signal by considering the effect of the gauge volume geometry as well as the influence of the material absorption on the average information depth is proposed. It is demonstrated that data evaluation requires a three‐dimensional least‐squares fit procedure in this case. Furthermore, possible aberrations and their impact on the analysis of the residual stresses by applying the `modified stress scanning' method are treated theoretically.